Multi-objective optimization of resource allocation in the project portfolio selection process: An integrated FAHP-MCGP approach - Wang Xiong (2022)
Internal audit is a function that provides independent and objective assurance and consulting services to business partners. Planning internal audit activities by selecting important audit projects and deploying appropriate resources enables audit function to use constrained resources effectively and efficiently. However, studies on internal audit planning have limited exposure in the literature. Moreover, prior research only focused on partial processes of the internal audit planning and was only concerned with risk management goal, which mainly applied ranking methods to prioritize candidate projects. To the best of our knowledge, a comprehensive and robust model has not been established to address the decision-making problems associated with the audit planning process. To fill these gaps, an integrated multi-stage framework is presented to develop a solid risk-based internal audit plan. The proposed framework begins with the risk assessment of auditable areas using FAHP, a combination of fuzzy comprehensive evaluation (FCE) and analytic hierarchy process (AHP). The next stage is to select project portfolio and allocate audit resources simultaneously through weighted multi-choice goal programming (Weighted MCGP) approach, minimizing aggregate deviations for multiple value-added objectives including risk mitigation. The third stage is to assign staff to the selected projects by balancing auditor preference and suitability of auditors for projects via MINMAX MCGP model. Finally, an audit schedule is displayed by creating a Gantt chart. A case study is performed to demonstrate the feasibility and validity of the proposed methods. The results show that the designed framework is a useful tool for internal audit planning and has promising practical application in various selection and allocation problems.